Representasi Pesan Edukasi Dalam Iklan Di Youtube (Studi Semiotik Roland Barthes Pada Iklan Konditioner Pantene) - Annisa Ramdhania; Zinaida, Rahma Santhi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
This researcher discuss Pantene conditioner advertisement because within 24 hours this advertisement was witnessed by 950,773 viewers and it was stated by the Pantene Indonesia Senior Brand Manager that product sales increased and made this conditioner product run out everywhere. This research is a qualitative and descriptive research. The researcher uses Roland Barthes' theory to understand the meaning in pantene advertisements and the audience who watches the advertisement for an invitation to buy a product. The Pantene Hair Miracles Treatment Conditioner advertisement tells about uncontrolled emotions due to fatigue, this then affects the social life of Keanu's character. However, after being angry and nagging, no solution was found for his uncontrollable emotions, after discussing with voice over it was found that it could be the source of all his emotions and anger, it was hair that was tired and needed treatment so that it could be recharged. The visuals and audio displayed through the analysis table show that as humans, we have a responsibility to take care of ourselves. Visuals and audio that have been analyzed using Barthes Semiotics also show the importance of not being emotional because emotions will only add to the chaos and not find a solution to a problem. Visuals and audio that have been analyzed in the table of research results also show educational messages about the process of self-improvement.